Evropski zeleni dogovor in pomanjkljivosti zelenega prehoda - Ferčič, Aleš (Podjetje in delo, 2025)
The author addresses the deficiencies of the green transition as defined by the European Green Deal and related acts. The fundamental issue highlighted is the lack of effective legal regulation on the restriction of natural resource use. In this context, the author points out formal-organizational and substantive issues that would arise if a political decision were made for such regulation, thereby creating opportunities for a genuine green transition based on the concept of eco-centric sustainable development. The author’s focus is directed to issues related to the EU’s competence for lawful action, the fields of this action or EU policy, the associated legal basis, and the type of (legal) act that would determine this action.
Keywords: decarbonization; dekarbonizacija; dematerializacija; dematerialization; European Green Deal; Evropski zeleni dogovor; green transition; omejevanje uporabe naravnih virov; restriction of natural resource use; sustainable development; trajnostni razvoj; zeleni prehod